Counteracting Urban Heat Island Effects in a Global Climate Change Scenario - Musco, Francesco (Springer International Publishing : Imprint: Springer, 2016)
Urban Heat Islands (UHIs) are a microclimatic phenomenon which manifests as a significant increase in the temperature of cities compared to their surrounding areas. Recently the phenomenon has been enforced by the tendency to climate change and in particular by extreme climate events. This book presents and analyzes the results of a project to develop and apply mitigation and adaptation strategies and measures for counteracting the global urban heat islands phenomenon, supported by the EU's Central Europe Regional Development Fund. Pilot studies were carried out in eight metropolitan areas: Bologna/Modena, Budapest, Ljubljana, Lodz, Prague, Stuttgart, Venice/Padua, and Vienna. The project involved feasibility studies and strategies for appropriately altering planning rules and governance to tackle the problem of UHIs, and focused on the specific morphology of EU urban areas, which are often characterized by the presence of historical old towns. The first part of the book is devoted to evidence, measures and tools, including tools to facilitate UHI analysis and decision support systems. The second part explores measures for counteracting urban heat islands, including specific analysis of the case studies and offering solutions for European cities. The volume includes supplemental materials such as references, glossaries and keyword lists. The UHI management plans developed here can be integrated into national and regional sustainable development approaches for urban and land planning. They can also contribute to the application of innovative urban planning techniques that foster a new "climate proof" planning approach in European cities. UHI project has been implemented through the CENTRAL EUROPE Programme co-financed by the ERDF.